Aflp Assessment of Ficus Cultivars for Identification and Conservation - Ali, Shaymaa H.; Jubrael, Jaladet M. S. (Science Journal of University of Zakho, 2013)
The fig (Ficus carica L., Moraceae), a typical Mediterranean fruit crop, is characterized by large adaptive potentialities to various ecological areas. To create a molecular characterization for 16 cultivars of Ficus, five  primer combinations were used to amplify these cultivar’s genomic DNA, producing a total of 292 legible bands (markers) were revealed, of which 281(96%) distinct polymorphic band patterns. The genetic diversity among 16 cultivars of fig ranged between 0.2124-0.7154. The lowest genetic distance was found between Qashe kani and Arzani where as the highest genetic distance was found between Qarani rash and Ribari. Cluster analysis by Using UPGMA method based on the similarity coefficient, cultivars were separated into seven major genetic clusters which were named as (F1, F2, F3, F4, F5, F6 and F7) with many sub-clusters. The analyzed data illustrates a good variability in the genetic pool of the local common fig making it a valuable source for incorporation into potential breeding programs for the region.
Keywords: Fig (Ficus carica); AFLP; genetic similarity